The Degree of Importance and Practice of Leadership Regarding "Leadership DNA" Model for Public Secondary School Principals in Zarqa Governorate as Perceived By their Teachers - Al-Omari , Aieman; Abu-Alaia, Mohammed (Jordan Journal of Educational Sciences, 2016)
The study aimed to identify the degree of importance and practice of leadership for school principals in Zarqa Governorate in regards to the "Leadership DNA Model" as perceived by teachers. The sample consisted of (280) teachers chosen stratified randomly. The questionnaires consisted of four dimensions, each dimension consisted of three fields. Results showed that the degree of importance of leadership was high, and the practice was average regarding to the "Leadership DNA model". There were no significant differences in the average differences among sample responses to the degree of importance and practice of leadership due to the respondents’ sex, educational qualification, and experience in education